Text comprehension at school: Is the application of graphic organizers still important to develop it? - Salazar-Rodríguez, Ana María (2020)
Research on graphic organizers and reading comprehension has taken up new reins in the knowledge about the reader's mental processes, but it has been avoided to understand the levels in the reading process. The importance of organizers often focuses on the power they demonstrate to allow the reader to analyze and map ideas, especially concept maps and mind maps. In this study, we propose to determine the effects of graphic organizers on text comprehension at the school stage. The study is quantitative of quasi-experimental design. It was developed in 42 students from the primary level of Callao, Peru. The results allow concluding that the graphic organizers improved the comprehension of texts in general. The evidences remit significant differences with scores compared at the literal level. The results of inferential understanding presented data that revealed improvement, although it was minimal at this level. This shows that graphic organizers can make improvements but are unlikely during the inferencing process. This shows that graphic organizers can make improvements but are unlikely during the inference-making process as in critical construction. Their contribution is essential in the literal processes, but it is suggested to replicate the study analyzing the processes of understanding at a higher level, with tests of greater complexity, to overcome the limitations obtained here.